2019
DOI: 10.4103/ijnmr.ijnmr_100_18
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate care challenges and barriers in clinical nurses: A qualitative study

Abstract: Background: Compassion is the heart of nursing care. Barriers to compassion in nursing may be influenced by the prevailing culture and religion of a society. Determining the barriers to providing compassion-based care would help nurses to plan better and more appropriate interventions. This study aimed to explore the challenges and barriers to compassionate care in nurses. Materials and Methods: This ethnographic study was performed in 2014–2016. The study participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…In this line, in studies by Brito‐Pons et al (2018a) and Oshidi et al (2019), work overload and continuous cost‐containment policies are identified as barriers to the delivery of truly compassionate care. In a study by Babaei and Taleghani (2019), the lack of a comprehensive care model is pointed out as an impediment to the implementation of compassionate care. Compassionate care may also be prevented by organizational barriers, as detailed in a study by Valizadeh et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, in studies by Brito‐Pons et al (2018a) and Oshidi et al (2019), work overload and continuous cost‐containment policies are identified as barriers to the delivery of truly compassionate care. In a study by Babaei and Taleghani (2019), the lack of a comprehensive care model is pointed out as an impediment to the implementation of compassionate care. Compassionate care may also be prevented by organizational barriers, as detailed in a study by Valizadeh et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Compassion is actually a constructive response to the suffering of others, and it can improve responses to treatment, preserve the dignity of patients, and facilitate self‐care in the individuals who provide it (Brito‐Pons and Librada‐Flores, 2018b). Compassion is one of the core elements of nursing care (Straghair et al 2019; Babaei and Taleghani, 2019): it is an attitude that generates sensitivity to suffering and a genuine desire to alleviate it; it enhances comprehensive care, high‐quality care, and provides a satisfying experience in the conduct of the profession (Brito‐Pons et al, 2018a; Sacco et al 2015). However, in their daily work, nurses are exposed to traumatic situations, disfigurements, frailty, hopelessness, tragedy, pain, suffering, and death, which puts them at risk of developing compassion fatigue (CF) (Boyle 2016; Fallek et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…16 Patient's education and awareness can reduce their worries and stress and enable them to participate in their caring process. 22 One way to get information about the patient's conditions is the family members' attendance in the doctors and nurses' visiting of the patient. Au et al, indicated that family members had positive experiences with their participation in the doctors and nurses' round of their patient.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] The previous studies have shown that nurses who work in overly stressful conditions are more prone to mental and physical exhaustion. [ 16 ] Nurses who work in these sectors face environmental stress, high workload, resource constraints, lack of managerial support, and difficult care conditions for patients, which affect the nursing care process and can jeopardize the quality of nursing care. Numerous studies have been performed on compassion satisfaction and compassion fatigue in nurses worldwide.…”
Section: Introductionmentioning
confidence: 99%